READINESS TO CHANGE OF HOME TAILORED ENTREPRENEURS IN TECHNOLOGY-BASED PERSPECTIVE - Iwan Hermawan; Sartono Sartono; Gita Hindrawati (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2021)
Flexibility to face changes in line with digital development and business challenges in market turbulence, exchange rates, and pandemic must be held by an entrepreneur to survive today. Entrepreneurs should manage tangible assets such as information technology (IT) and intangible assets such as knowledge inherent in human capital. Both processes will build resilience and foundation toovercome changes as complex as any future business challenges. IT as a knowledge infrastructureneedsactivities support in processing, protecting, and distributing within organizational entities such as knowledge-sharing (KS). The existence of robustKS in the organization atmosphere encourages entities to be more cohesive in organizational learning, builds individual capability and creativity, and solves many work-life problems, which is related to the readiness of entrepreneurs to face change. The purpose of this research is to bridge inconclusive problem gaps between the effect of ITon readiness to change (RTC) by offering KS mediation. It is confirmatory research with a quantitative Structural Equation Modeling approach by taking 151 samples. The respondent ishome tailor entrepreneurs in the SMEs area. This study empirically proves that KS can be a partial mediator to leverage the role of IT on RTC.Flexibility to face changes in line with digital development and business challenges in market turbulence, exchange rates, and pandemic must be held by an entrepreneur to survive today. Entrepreneurs should manage tangible assets such as information technology (IT) and intangible assets such as knowledge inherent in human capital. Both processes will build resilience and foundation toovercome changes as complex as any future business challenges. IT as a knowledge infrastructureneedsactivities support in processing, protecting, and distributing within organizational entities such as knowledge-sharing (KS). The existence of robustKS in the organization atmosphere encourages entities to be more cohesive in organizational learning, builds individual capability and creativity, and solves many work-life problems, which is related to the readiness of entrepreneurs to face change. The purpose of this research is to bridge inconclusive problem gaps between the effect of ITon readiness to change (RTC) by offering KS mediation. It is confirmatory research with a quantitative Structural Equation Modeling approach by taking 151 samples. The respondent ishome tailor entrepreneurs in the SMEs area. This study empirically proves that KS can be a partial mediator to leverage the role of IT on RTC.